"C"ing the light - assessing code comprehension in novice programmers using C code patterns - Glasauer, Christina; Yeh, Martin K.; DeLong, Lois Anne; Yan, Yu; Zhuang, Yanyan (Computer science education, 2025)
Feedback on one's progress is essential to new programming language learners, particularly in out-of-classroom settings. Though many study materials offer assessment mechanisms, most do not examine the accuracy of the feedback they deliver, nor give evidence on its validity. We investigate the potential use of a preexisting set of C code snippets as the basis for a high-quality C programming ability assessment tool. We utilize the Rasch Model and the Linear Logistic Test Model to evaluate the validity and accuracy of the code snippets and to determine which C operations contribute most to their overall difficulty. Our results show that these code snippets yield accurate assessments of programming ability and reveal the degree of difficulty associated with specific programming operations. Our results suggest that the code snippets could serve as the basis for sophisticated, valid, and fair code comprehension skill assessment tools.